CITIZEN DIPLOMACY PRACTICES AT THE HAGUE: AN ANALYSIS OF THE STICHTING TONG-TONG’S ROLE FROM 2009 TO 2023: Praktik Citizen Diplomacy di Den Haag: Analisis Peran Stichting Tong-Tong Tahun 2009-2023 - Farra Fauziah Nurrahmah; Saviq Isnu Balkhi; Sarah Lydwina Olivia Sinaga; Ario Bimo Utomo (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to analyze the role of the Tong-Tong Foundation as a non-state actor in the practice of citizen diplomacy in The Hague, Netherlands. The Tong-Tong Foundation (Stichting Tong-Tong) is the oldest cultural organization in the Netherlands. The establishment of the Tong-Tong Foundation aims to promote Eurasian Indies culture and provide an understanding for the Indonesian people about its cultural history. The research method used is descriptive qualitative, with secondary data collection techniques through literature studies. Data collection for this study uses secondary data through literature studies obtained through previous journal articles and the official website of the Tong-Tong Foundation itself. The author sets the selection period as 2009-2023. The selection of 2009 was due to a name change by the Tong-Tong Foundation and 2023 was the last year the Tong-Tong Foundation was active. The author obtained research results in the form of citizens or community groups can play a role in diplomatic activities and the Tong-Tong Foundation has a good impact as a non-state actor in Indonesia-Netherlands relations through its role as a citizen diplomacy actor by Paul Sharp.